User Centered Concept Development of a Hybrid Ski Binding - Ohlslöf, Anton; Ågren, Hampus (My University, 2022)
Abstract The aim of this study was to understand the strength and weaknesses of current hybrid ski bindings, based on user centered research and benchmarking. Further on, to develop a high performance binding concept, based on the identified market gaps and user insights. After the conducted research a thorough market analysis and user segmentation could be presented. These results were further synthesized into a product statement explaining what the design concept set out to achieve: The product should be a trustworthy and robust solution that provides the user with full alpine performance and touring possibilities. Through a transparent construction and self explanatory interactive features, the user should be able to seamlessly switch between ride modes and spend as much time as possible skiing. The resulting concept is in essence an alpine binding toe piece with a modular pintech attachment positioned on top. It is a product with a separation of functions that embodies the need for robustness and ease of use found throughout the research. Positive aspects of the design are the low Stack height in Ski mode, multi-directional elasticity and easy changing of modes. While the negatives are the high stack height in touring mode along with the exposed pintech attachment in ski mode. The conclusion was therefore drawn that the proposed solution is a viable option to bring to market, but the stack height in touring mode needs to be further evaluated along with prolonged durability testing of a prototype strong enough for the slopes. 4